Resistance of flow over submerge pillar of different surface roughness - an experiment / Ahmad Haiqal Abd Rahman - Abd Rahman, Ahmad Haiqal (2022)
This impact force could not only alter the dynamic load pattern on the pillar, but it could also cause significant structural vibration. The precise effect of roughness on fluid flow is unknown, but a working estimate has been offered by a number of authors over time. to investigate the relationship between surface roughness of pillar and flow over a submerged body using Circulation Water Channel. The application that will be used for this experiment is a circulation water channel. The purpose of the circulation water channel is to teach the fundamentals of fluid mechanics as they relate to hydraulic flow. According to the experiment, the flow of water around the pillar should increase as the velocity of water increases. To clarify the phenomenon, the graph of water flow rate is directly proportional to water velocity. When static analysis is performed on the pillar around which the wave flows in a stable state, the influence of fluid-structure coupling effect can be ignored.